(untitled) (PUBMET, 2023)
The PATTERN project, officially known as "Piloting open and responsible Activities and Trainings Towards the Enhancement of Researchers Networks," is a comprehensive initiative funded by the European Commission under the Horizon Europe programme. Its primary focus is to advance open and responsible research and innovation (Open RRI) across Europe through training for researchers to enhance their capacity for effectively addressing societal challenges while promoting transparency and inclusivity in research. The project spans 42 months and involves a total of 19 organisations and institutions from 13 European countries, including the Ruđer Bošković Institute in Croatia, contributing to the development and implementation of training programs tailored for researchers at all career stages. PATTERN’s training modules cover a diverse range of topics vital to open RRI, including open access, FAIR data management, citizen science, research integrity, gender equality, non-discrimination, inclusion in research, dissemination and exploitation of results, science communication, and management and leadership skills. By addressing these crucial aspects, the PATTERN project aims to equip researchers with the knowledge and skills necessary to excel in today’s dynamic research landscape. The project’s implementation began by systematic mapping and comprehensive analysis of contemporary educational opportunities for researchers on Open RRI, after which comes the development of innovative curricula, with an emphasis on inclusivity and fairness in the modules. Implementation and testing are integral components of PATTERN’s strategy. The project intends to test its training modules through a variety of tailored activities conducted by nine core partners and five associated institutions, which will act as pilot institutions across Europe. PATTERN’s expansive network includes Croatia, Finland, Greece, Hungary, Ireland, the Netherlands, Portugal, and Turkey. This network, encompassing OpenAIRE members and National Open Access Desks (NOADs), ensures a broad and diverse reach for the project’s training curricula. Crucially, PATTERN will establish a digital platform, where all training materials will be openly accessible, providing a solution for hosting and disseminating freely available training modules. This platform will not only facilitate knowledge sharing but also mobilise and moderate the research and innovation community. It will serve as a valuable resource for relevant bodies and institutions responsible for educating researchers, disseminating project results, and promoting OS practices in multiple languages. Based on the accumulated knowledge and insights, a series of policy recommendations will be designed and developed, targeting European Union bodies, national entities, higher education stakeholders, and research institutions, ultimately promoting open and responsible research practices at a systemic level. There is an ongoing demand for training and promotion of open science (OS) topics in Croatia among researchers, with a notable deficiency in formal OS education within Croatian higher education institutions. To bridge this gap and promote OS practices effectively, PATTERN leverages a wealth of expertise accumulated through EU projects that have laid the groundwork for comprehensive training programs designed to enhance researchers’ competencies. The PATTERN project represents a pioneering effort to advance open and responsible research and innovation practices in Europe. With active participation from institutions such as the Ruđer Bošković Institute, PATTERN aspires to empower researchers and institutions alike. By developing comprehensive training modules, creating a collaborative platform, and providing policy guidance, PATTERN is poised to contribute significantly to the advancement of science and society in the European Research Area.